Moore and Wittgenstein on certainty - Stroll, Avrum, 1921-2013 (Oxford University Press, 1994)
Ludwig Wittgenstein's On Certainty was finished just before his death in 1951 and is a running commentary on three of G.E. Moore's greatest epistemological papers. In the early 1930s, Moore had written a lengthy commentary on Wittgenstein, anticipating some of the issues Wittgenstein would discuss in On Certainty. The philosophical relationship between these two great philosophers and their overlapping, but nevertheless differing, views is the subject of this book. Both defended the existence of certainty and thus opposed any form of scepticism. However, their defences and conceptions of certainty differed widely, as did their understanding of the nature of scepticism and how best to combat it. Stroll's book contains a careful and critical analysis of their differing approaches to a set of fundamental epistemological problems.